Current Review of Genetically Modified Lactic Acid Bacteria for the Prevention and Treatment of Colitis Using Murine Models - Alejandra de Moreno de LeBlanc; Silvina del Carmen; Jean-Marc Chatel; Anderson Miyoshi; Vasco Azevedo; Philippe Langella; Luis G. Bermúdez-Humarán; Jean Guy LeBlanc (Gastroenterology Research and Practice)
Inflammatory Bowel Diseases (IBD) are disorders of the gastrointestinal tract characterized by recurrent inflammation that requires lifelong treatments. Probiotic microorganisms appear as an alternative for these patients; however, probiotic characteristics are strain dependent and each probiotic needs to be tested to understand the underlining mechanisms involved in their beneficial properties. Genetic modification of lactic acid bacteria (LAB) was also described as a tool for new IBD treatments. The first part of this review shows different genetically modified LAB (GM-LAB) described for IBD treatment since 2000. Then, the two principally studied strategies are discussed (i) GM-LAB producing antioxidant enzymes and (ii) GM-LAB producing the anti-inflammatory cytokine IL-10. Different delivery systems, including protein delivery and DNA delivery, will also be discussed. Studies show the efficacy of GM-LAB (using different expression systems) for the prevention and treatment of IBD, highlighting the importance of the bacterial strain selection (with anti-inflammatory innate properties) as a promising alternative. These microorganisms could be used in the near future for the development of therapeutic products with anti-inflammatory properties that can improve the quality of life of IBD patients.